Institution Strategy Remodel of Assunniyyah Pesantren in Jember and Kyai Syarifuddin Pesantren in Lumajang - Ba’its Sulthon, Moh.; Halim Soebahar, Abd.; Hepni, Hepni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This article discusses a social change in Jember, especially in Kencong and Lumajang, by capturing changes in the community around Assunniyyah Pesantren and Syarifuddin Pesantren. The institution remodels and differentiation as happened in Jember and Lumajang show a progressive role of pesantren. In pesantren approach, Islam is applied under the situations and conditions in which the community lives. The pesantren strategy remodel is evolutionary. Changes are made gradually and naturally following society's rules and pesantren contribution. Change is not related to vision, mission, and values. The pesantren hold a vision, mission, and basic values ​​starting from the first time to the present. The pesantren institutional strategy remodel is inclusive. The pesantren experience changes from authority aspect, structure, and work mechanisms. The pesantren adopt innovations as long as they do not conflict with the organization.